2011
DOI: 10.1088/1468-6996/12/3/034410
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission and glow discharge properties of 12CaO·7Al2O3electride for fluorescent lamp applications

Abstract: 12CaO·7Al 2 O 3 electride, a sub-nanoporous compound having a work function of 2.4 eV, was examined as a candidate cathode material in fluorescent lamps. The electron emission yield was higher and the discharge voltage was lower for 12CaO·7Al 2 O 3 than for existing cathode materials such as Ni, Mo or W; therefore, the energy consumption of the fluorescent lamps can be improved using 12CaO·7Al 2 O 3 cathodes. Prototype glow-discharge lamps using 12CaO·7Al 2 O 3 were constructed and exhibited reasonable durabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 56 publications
(62 reference statements)
1
36
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30][31] Electrides are a novel kind of ionic compound in which electrons serve as the anions. [32][33][34][35] With such a unique structure, electrides show great potential in various applications, such as superconductivity, 36,37 electronics, [38][39][40] and catalysis. [41][42][43] Recently, theoretical investigations by Li et al have shown that systems in which the excess electrons are diffuse exhibit great NLO responses.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31] Electrides are a novel kind of ionic compound in which electrons serve as the anions. [32][33][34][35] With such a unique structure, electrides show great potential in various applications, such as superconductivity, 36,37 electronics, [38][39][40] and catalysis. [41][42][43] Recently, theoretical investigations by Li et al have shown that systems in which the excess electrons are diffuse exhibit great NLO responses.…”
Section: Introductionmentioning
confidence: 99%
“…While electrides have recently attracted some interest for use in synthetic 7,8 and photonics 9,10 applications, there have been relatively few theoretical studies of these materials. Of the two previous DFT studies, Singh et al 2 considered the simplest organic electride with known crystal structure, Cs + (15-crown-5) 2 e À , and Sushko et al 11 examined the single inorganic electride [Ca 24 Al 28 O 68 ] 4+ 4e À .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SEE from solid materials, in which slow SEEs are emitted only from within a thin surface layer at most hundreds of angstrom thick, in porous dielectrics the thickness of the layer from which slow SEEs are emitted reaches tens and hundreds of microns, and an electric field of 10 4 –10 5 V cm −1 , which expels the slow electrons from the material, forms within these layers . The role of the electric field is to balance the losses of the slow electrons due to scattering by phonons within the pore walls by accelerating these electrons inside the pore, thereby lowering their recombination probability .…”
Section: Resultsmentioning
confidence: 99%